Academia journal of biology Volume 42, Number 2 (H. Vietnam academy of science and technology, 2020)
Contents: An updated list of Monogenoidea from marine fishes of Vietnam; New record of the genus Parkellus Jairajpuri, Tahseen & Choi (Mononchida: Mononchidae) with redescription of Parkellus menzeli male in Vietnam; Food selection of maize weevil Sitophilus zeamais (Motschulsky);...
Formerly Tạp chí sinh học (Journal of Biology)
Keywords: Sinh học; Tạp chí